Are measures of marital satisfaction valid for women with depressive symptoms? The examination of factor structure and measurement invariance of the Couple Satisfaction Index‐4 across depression levels in Portuguese women. (14th January 2020) - Lamela, Diogo; Figueiredo, Bárbara; Morais, Ana; Matos, Paula; Jongenelen, Inês
Abstract: Marital satisfaction (MS) is a key indicator of mental and physical health. Factor structure of MS measures in individuals with clinical levels of depression as well as their measurement invariance across groups with different levels of depressive symptoms were not yet explored. The lack of evidence of measurement invariance might compromise valid comparisons between individuals with elevated and minimal depressive symptoms in MS. This study examined the factor structure of the Couple Satisfaction Index‐4 (CSI‐4) among women with clinical levels of depression, tested the CSI‐4 measurement invariance across depression levels groups, and investigated CSI‐4 convergent and divergent validity. Participants were 891 heterosexual married/cohabiting women who were assigned into one of two groups based on assessment of their levels of depressive symptoms. Participants completed the CSI‐4 and self‐reported measures used to examine convergent and divergent validity. Support was found for the factor structure of the CSI‐4 for the total sample and both elevated depressive symptoms and minimal depressive symptoms groups. Subsequent multigroup confirmatory factor analyses supported the measurement invariance of the CSI‐4 across depression levels groups. The CSI‐4 revealed excellent values of internal consistency and convergent and divergent validity. Our findings suggest that CSI‐4 produces comparable response patterns across depression groups and thus meaningful comparisons between groups can be performed.